Towards a typology of university technology transfer organizations in China: Evidences from Tsinghua University - Han Zhang; Yuzhuo Cai; Zhengfeng Li (Triple Helix, 2018)
This paper argues that failure to deeply understand various existing organizations of university-industry technology transfer in China impedes the progress of both practice and research on technology transfer between university and industry in that country. In response, it attempts to categorize different types of university technology transfer organizations in China in over a 30-year time span and analyze the relations between these organizations. In so doing, Tsinghua University is taken as an example for analysis, because technology transfer at Tsinghua University can be seen as a microcosm of university-industry technology transfer in China with pioneer practices and successful experience to be followed by other universities in China. The analysis is guided by an analytical framework, constructed by integrating the insights from relevant literature. The framework distinguishes between different forms of university technology transfer organizations by focusing on six dimensions of the organizational characteristics. After identifying eight types of university technology transfer organizations in Tsinghua University with detailed descriptions of their respective organizational characteristics, the paper further groups them into a four-category typology. Besides its contribution in constructing a framework to understand university technology transfer organizations in the Chinese context, the paper also solicits suggestions for Chinese and international stakeholders who may potentially cooperate with Chinese research universities in research, development, and innovation.
Keywords: 330; Technology transfer; Innovation; University and industry interaction; Tsinghua University; China